Teaching Reading through Reciprocal Teaching Strategy - Afrizatama, Deni (Universitas Swadaya Gunung Jati, 2016)
This is experimental research with quantitative approach to analyse the data. Quasi experimental is used to gain the data by using the matching only pretest – postest control group design.Tne main ptirpose of tnis researcn was intended to find out whether reciprocal teaching strategy in teaching reading for the eighth grade at SMPN 10 Kota Cirebon is effective or not and what the students’ response in learning reading using reciprocal teaching strategy are. In this research. The population of this research was eighth grade students of SMPN 10 Kota Cirebon in the 2015/2016 academic year. The number population is about 270 students consisted of nine classes and each class consisted of 25 – 30 students. This research only took two classes as sample, VIII H as control class and VIII I as experimental class. There were two research instruments that was used to gather the data: Test (Pre-test and Post-test) was used to find out the students’s achievement in reading before and after teaching reading by using reciprocal teaching strategy and questionnaire was used to find out the students’ response about learning reading using reciprocal teaching strategy. After collecting the data, the data was analyzed by using t-test formula from fraenkel to find out t-account. The result of the test showed that t-account was 4.47 and t-table was 2.012 with (df) 48 and significant level 0.05 (5%). It means that t-account (4.47) is higher than t-table (2.021). It can be concluded that (Ha) “Reciprocal teaching strategyis effectivein teaching reading for the eighth grade at SMPN 10 Kota Cirebon.” is accepted.